Sugar beet root growth under different watering regimes: a minirhizotron study - Fitters, Tamara F.J.; Mooney, Sacha J.; Sparkes, Debbie L. (Elsevier, 2018)
The yield of sugar beet is often reduced by drought stress and it has previously been shown that water uptake, especially from deeper layers of the soil profile, may be limited by inadequate total root length. Experiments were conducted to assess root growth at different depths in response to specific watering regimes. Sugar beet plants were grown in wooden boxes (2.16 m2 × 1.2 m) in a polytunnel in two consecutive years. Minirhizotrons allowed regular monitoring of root growth at five different depths. Only when water in the upper soil layers had been depleted, did roots start proliferating in deeper soil layers. This development of the root system architecture, together with a lag between roots arriving at depth and actively taking up water, led to a delay in water being extracted from those deeper layers. During the period when roots were proliferating at depth, stomatal conductance reduced, indicating that the plants were suffering from water stress despite there still being water available. Even though new soil layers with high water availability were explored the stomatal conductance did not recover.